"The Senses Pointing towards a New Transformation": On Touch, Collectivity, and Lygia Clark's The I and the You at the First International Tactile Sculpture Symposium, 1969. Issue 1 (2nd January 2023) - Carter, Kristen
Abstract: In 1969 Lygia Clark and Hélio Oiticica travelled to Los Angeles to participate in the first International Tactile Symposium. Led by August Coppola and hosted by the University of California State-Long Beach, this event set out to explore the collective facets of touch and its relation to art. On the one hand, the symposium's drive to collaborate through somaesthetic experience resonated with the countercultural ethos of the 1960s, exposing desires for community and authentic experience. On the other hand, I ask how the antagonisms found in Clark's exhibited proposition, The and the You (1967), open a different line of inquiry into the ways in which the phenomenological concerns of touch and the socialized body resonated with mounting debates regarding the viability of collective experience in the United States. By mapping these different interpretations—made evident in the literature around the symposium, including an unpublished essay written by Oiticica for the event—I consider how the symposium held together distinct and sometimes competing ideas of what touch and collectivity could mean at the time. As much as touch offered playful opportunities to come together, it also made space to reimagine the active, relational unfolding of bodies as intersubjective, dispersed, and unevenly formed. I argue the symposium reveals a desire to find new, more meaningful art forms in light of socio-political uncertainty and change. It also offers a more nuanced history of relational art practices in the US, especially as they developed alongside shifting conceptions of personal freedom and collective agency.